The future of livestock and livestock production systems in Asia’s food security landscape - Alders, R.; Kalupahana, R.; Hung Nguyen-Viet; Rahman, Habibar; Unger, Fred; Wright, Iain A. (World Scientific Publishing, 2024)
The following sections are included: